PSIX-11 Impact of a phytogenic feed additive on growth performance, feed intake and carcass traits of finishing steers. (5th December 2019) - Brand, Tassilo; Hünerberg, Martin; McAllister, Tim; Saleem, Atef; Shen, YiZhao; Miller, Bryan; Yang, Wenzhu
Abstract: The purpose of this study was to evaluate the effect of a phytogenic feed additive (Digestarom® (DA), Biomin, Getzersdorf, Austria) on growth performance, feed intake, carcass traits, and liver abscesses of finishing beef steers. One hundred and twenty Angus × Charolais crossbred steers (initial BW 488 ± 26.5 kg) were used in a 110-d feeding experiment. Steers were blocked by weight and randomly assigned to 12 pens with 10 steers per pen. Each pen was allocated to 1 of 3 diets. Each diet contained 86.5% barley, 10.0% barley silage and 3.5% vitamin and mineral supplement on a dry matter basis. Digestarom® replaced barley grain in the vitamin and mineral supplement at 1.41 and 2.82 g/kg, to achieve average daily intakes of DA of 0 (Control), 0.5 (LowDA) and 1.0 g (HighDA) per steer. Diets were prepared once daily and offered ad libitum intake. Two pens per treatment were equipped to record individual feed intake ehavior. Steers were weighed every 28 d and carcass traits and liver scores were recorded at slaughter. Dry matter intake (average 9.34 kg/d) and final BW (average 669 kg) did not differ among treatments. Average daily gain (ADG) tended (P < 0.09) to increase in response to DA supplementation (control, 1.82; LowDA, 1.87; and HighDA, 1.95 kg/d), but gain:feed ratio was not affected. Supplementation of DA affected rib-eye area quadratically (P < 0.05) with the largest area observed for LowDA. Total abscessed livers were not affected, whereas proportion of severe liver abscesses was numerically lower (P < 0.15) with DA (31 and 43% for LowDA and HighDA, respectively) compared to the control (50%). The positive effect of DA on ADG and percentage of severely abscessed livers should be validated in larger scale feedlot studies.